Prevalencia y Factores Epidemiológicos asociados de la Infección del Tracto Urinario en Gestantes. Centro de Salud Pampa Cangallo. Ayacucho 2015 - Loayza Silva, Elena Marisol (2019)
In the present retrospective transverse investigation was determined the prevalence and associated epidemiological factors of Urinary Tract Infection (UTI) in pregnant patients that were treated at the Pampa Cangallo Health Center from February 1 to August 31 of 2015, For which data from a sample of 152 clinical histories were collected using a data collection sheet that met the inclusion criteria. The 152 pregnant women had an average age of 27 years, an average of 23 weeks of gestation, 60.5% were of cohabiting civil status, 56.6% of secondary education, 57.9% came from the city of Pampa Cangallo, 43.4% were multifaceted, 69.1% were of normal nutritional status at the beginning of pregnancy and 44.7% were in the third trimester of pregnancy; pregnant women with UTI presented similar characteristics. A prevalence of Urinary Tract Infections (UTI) was determined at 65.1%. Statistical association between urinary tract infections in pregnant women was found with the degree of instruction, vaginitis and recurrent UTI.